2012
DOI: 10.1063/1.4764216
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hypernuclear nonmesonic weak decay

Abstract: Abstract. Simple and coincidence spectra of the NM weak decay of light hypernuclei have been evaluated in a systematic way for the first time. We have only considered 1N induced processes, neglecting entirely the events induced by 2N emission, as well as the effects of the FSIt's. As the theoretical framework we have used the IPSM with three different parametrizations for the transition potential. The comparison with data strongly suggests that the soft π + K exchange model could be a good starting point to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The dominant role is being played by the exchange of pion and kaon mesons (PKE). We have recently shown that the π + K meson exchange potential with soft dipole form factors (SPKE) reproduces fairly well both s-shell [10], and p-shell [11] NMWD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant role is being played by the exchange of pion and kaon mesons (PKE). We have recently shown that the π + K meson exchange potential with soft dipole form factors (SPKE) reproduces fairly well both s-shell [10], and p-shell [11] NMWD.…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the CRISP code has been used to simulate nuclear reactions of several kinds, such as those induced by protons [33][34][35], photons [19,27,[36][37][38], electrons [39,40], or hypernuclei [21,41,42], with energies from 50 MeV up to 3.5 GeV, and on nuclei with masses going from A = 12 up to A = 240 and with several observables: spallation products, strange particles, fission products, hyperon-decay particles, fragment mass, and atomic number distributions. The code has been applied in the study for development of nuclear reactors [43][44][45].…”
Section: -3mentioning
confidence: 99%
“…Nas altas energias, o fóton apresenta uma componente hadrônica na sua função de onda que aumenta a seção de choque de interação com os nucleons. De acordo com o modelo de dominância vetorial (VMD) [18][19][20][21], no meio nuclear, a seção de choque totalé dominada pela produção de O código CRISP tem obtido bons resultados no estudo de reações induzidas por prótons [45,46,66,67], fótons [17,44,55,68], elétrons [69,70] e processos que dependem da cascata intranuclear, como a produção de káon [71] e o decaimento de hypernúcleos [72][73][74]. Os processos de evaporação/fissão estudados com o código obtiveram pela primeira Chapter 1.…”
unclassified